IMF Glossary : English, French, Arabic. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
This volume presents English, French, and Arabic words, phrases, and names of institutions most commonly encountered in IMF documents.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Informal Economy; Monetary Policy; Underground Econom